2018
DOI: 10.5664/jcsm.7048
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Trial Period With a Sleep Position Trainer in Patients With Positional Sleep Apnea

Abstract: Treatment with the SPT came with high adherence rates and was effective in reducing REI and supine sleep position. The trial period is in the patients' best interest, as it may prevent those who will not benefit from positional training from purchasing an SPT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 46 publications
2
8
0
Order By: Relevance
“…Recently positional devices have become available that are more comfortable and have objective adherence monitoring capability. 15,20,[21][22][23][24][25][26] The SPT is one such device. However, treatment efficacy and adherence with the SPT device had not been previously compared with positive airway pressure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently positional devices have become available that are more comfortable and have objective adherence monitoring capability. 15,20,[21][22][23][24][25][26] The SPT is one such device. However, treatment efficacy and adherence with the SPT device had not been previously compared with positive airway pressure.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of the device has been documented in several clinical trials. 15,[21][22][23][24][25][26] However, the relative effectiveness, adherence, and satisfaction compared to the gold standard of positive airway pressure treatment has not been tested in a group of patients with ePOSA. The purpose of this study was to demonstrate noninferiority of the SPT device compared to auto-adjusting positive airway pressure (APAP).…”
mentioning
confidence: 99%
“…Short- and long-term results of these devices showed a reduction in AHI combined with high compliance rates [ 99 , 105 ]. However, in real-life registries, <60% of the patients remains adherent, and only 25% are willing to purchase the device, related to poor objective results, intolerance to the vibrations, cost of the device, persistent symptoms or preference for another treatment option [ 106 , 107 ]. In general, patients expressed a preference for position training versus CPAP.…”
Section: Mechanical Obstructionmentioning
confidence: 99%
“…A recently reported study evaluated a 1-month trial period with a sleep position trainer (SPT) in patients with positional OSA. In the 79 adult patients who completed the study protocol, adherence was found to be 95 ± 8%, and 50% of patients were responders with a reduction on the respiratory event index [ 77 ]. This study did not evaluate pediatric patients.…”
Section: Adjuvant Therapy: Positional Therapymentioning
confidence: 99%